(untitled) (International Journal of Engineering and Computer Science, 2015)
A new technique is proposed for secure image transmission, which automatically transforms large-volume secret image into secret-fragment-visible mosaic image of the same size. The mosaic image is obtained by dividing the secret image into fragments and transforming their color characteristics to be those of the corresponding blocks of the target image. It looks similar to an arbitrarily selected target image and may be used as a camouflage of the secret image. We proposed a approach to enhance security of the mosaic image by providing better Encryption logic which provide faster encryption. And for the sake of transmission we proposed JPEG lossless compression technique which provide good compression ratio.